Power Quality Improvement Using Custom Power Devices in Squirrel Cage Induction Generator Wind Farm to Weak-Grid Connection by using neuro-fuzzy control - Kopella Sai Teja; R.B.R. Prakash (Institute of Advanced Engineering and Science, 2015)
Wind farm is connected to the grid directly.The wind is not constant voltage fluctuations occur at point of common coupling (PCC) and WF terminal . To over come this problem a new compensation strategy is used . By using Custom power devices (UPQC).It injects reactive power at PCC . The advantages of UPQC is it consists of both DVR and D-STATCOM . DVR is connected in series to the line and it injects in phase voltage into the line .D-STATCOM is connected shunt to the line .The internal control strategy is based on management of active and reactive power in series and shunt converters of UPQC . The power exchainge is done by using DC-link